Socioeconomic Factors with Nutritional Status of Toddlers - Risna Ayu Rahmadani; Ria Wahyuni; Darmi Arda; A. Suyatni Musrah; Riska Sabriana (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The nutritional status of toddlers is an important indicator of children's health and well-being. Good nutrition at an early age has a long-lasting impact on physical growth, cognitive development, and health throughout life. The nutritional status of toddlers reflects whether children are getting enough nutrients to grow and develop properly or are malnourished, which can result in various health problems. This study aims to determine socioeconomic factors with the nutritional status of toddlers—quantitative research design analytical survey with a cross-sectional study approach, with a Purposive Sample technique. Based on the Chi-Square test shows that the variable income has a p-value of 0.003, Maternal Knowledge p-value of 0.005, Maternal Education p-value of 0.690, and Maternal occupation p-value of 0.510. It can be concluded that there is a relationship between family income and maternal knowledge with the nutritional status of toddlers. There is no relationship between maternal education and work with a healthy group of toddlers. To improve the nutritional quality of toddlers, a comprehensive approach that considers various socioeconomic factors, education, and family welfare is needed. These programs should be designed and implemented based on research findings and the needs of the targeted communities.